Continuous false positive results by SARS-CoV-2 rapid antigen testing: a case report - Galipeau, Yannick; Xavier, Abishek; Dyks, Aaron; Cooper, Curtis; Langlois, Marc-André (Frontiers in Public Health, 2023)
Efficient and rapid identification of active SARS-CoV-2 infections has been key to monitoring and mitigating the spread of the virus. The implementation of nucleic acid testing (e.g., RT-PCR) was broadly adopted by most public health organizations at the national and community levels across the globe, which was followed by more accessible means of home testing including lateral flow immunochromatographic assay (LFA), also known as a rapid antigen test. Here we report the case of an adult female who repeatedly and consecutively tested positive by RAT (BTNX inc). This sustained false positive was not linked with an active SARS-CoV-2 infection, which was ruled out by RT-PCR and serological analyses. SARS-CoV-2 serology revealed no detectable levels of antibodies against the nucleocapsid suggesting no recent prior infection by SARS-CoV-2. This continuous false positive was limited to BTNX testing devices. This case report aims to describe that such continuous false positives can occur and describes alternative testing approaches that can be performed to confirm RAT results. In addition, broader awareness of such occurrences is warranted in the healthcare and public health community to avoid unnecessary negative impacts on individual’s day to day life.